Survey of the Antibodies to HTLV -1/2 Among Intravenous Drug Users in Thailand - Phoiampaisathit, Sukjai; Rotjanawiwat, Archawin; Wongcheree, Suthon; Saguanwongse, Suranga; Warachi, Pajit (Journal of Health Science of Thailand, 1994)
The human-T-cell leukemia-lymphoma virus type 1 (HTLV- 1) causes adult T-cell leukemia. lymphoma (ATLL) and HTLV-l associated Myelopathy. It appears to be spread worldwide. On the other hand, the prevalence of a second type of HTLV (HTLV-2) is high in intravenous drug users (IVDU) or other high risk group such as sexual transmitted disease patients. In this preliminary study, attempt was made to determine the antibody to HTLV-1/2 in a total of 300 HIV- positive plasma specimens from IVDU group from Thanyarak hospital which were screened by an Enzyme-Linked lmmunosorbent Assay (ELISA) Repeatedly reactive samples were further tested by western blot assay (WB) Of the 300 specimens, 10 plasma specimens were positive for HTLV anti bodies by ELISA as a screening test. while another 7 were found with absorbance to be near the cut-off value of 0.35. Seventeen specimens were conﬁrmed by western blot and interpreted according to manufacturer criteria. or these plasma specimens, only 5 were continued negative and the others 12 specimens were indeterminate. Thus,From this results. there was no indication that the antibody to HTLV-l/2 was found among the HIV-infected Thai lVDU.lt is therefore advisable that plasma specimens with indeterminate be supplementary tested by polymerase chain reactiona(PCR) for HTLV-l/2.